Diabetic nephropathy: modern principles of classification, diagnosis and features of antihyperglycemic therapy - A. G. Borisov; S. V. Chernavskiy; M. A. Smirnova; A. A. Stremoukhov (Лечащий Врач, 2021)
The article is devoted to modern approaches to the treatment of diabetes mellitus complicated by kidney damage. Diabetes mellitus is the most important problem of modern medicine, which is primarily due to the high prevalence of the disease among the working-age population. Diabetic nephropathy is one of the severe chronic complications of diabetes, which increases the disability and mortality of patients. Diabetic nephropathy is the main cause of the development of end-stage renal failure in developed countries and eventually affects about 30% of patients. Kidney damage in patients with diabetes occurs in 6-7% of cases out of the total number of nephropathies in patients receiving treatment in a specialized nephrological department of a multidisciplinary hospital. The first manifestations of diabetic nephropathy develop 3-4 years after the onset of the disease, and reach their peak in 15-20 years. The concept of «chronic kidney disease» includes kidney damage regardless of the primary diagnosis and is characterized by such basic diagnostic criteria as urinary albumin excretion and glomerular filtration rate values, which are markers of kidney damage. Methods for preventing the progression of diabetic nephropathy include general measures to change the lifestyle, control of glycemia and blood pressure, correction of lipid metabolism disorders in combination with nephroprotective therapy. Currently, when choosing therapy in patients with type 2 diabetes mellitus in combination with chronic kidney disease, along with taking metformin, preference is given to sodium-glucose cotransporter type 2 inhibitors and glucagon-like peptide-1 receptor agonists with a nephroprotective effect.